Pengaruh Kode Etik Bagi Guru Terhadap Kedisiplinan dan Pembelajaran di Satuan Pendidikan (SD, SMP, SMK) - C.A Astuti Darmiyanti; Mustopa Saripudin (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to examine the impact of a code of ethics on discipline and learning for teachers in elementary, junior high and high school education units. This type of research was carried out using research methods used in the literature search from various journals, proceedings and websites. The findings of this research reveal that the application of the teacher's code of ethics in the educational units specified in the discussion is generally very effective. Teachers have developed a code of ethics of professional honesty, obtain information about students, foster a positive school environment, and promote the quality and dignity of their vocation.